Specific heart muscle disease - Evans, Tom, 1942-; Symons, Cecil; Mitchell, Andrew G. (Wright-PSG, 1983)
Specific Heart Muscle Disease presents the primary syndromes in which heart muscle disease is an intrinsic part of another clinical syndrome. This book discusses the cardiomyopathies and shows how they are related to the different forms of specific heart muscle disease. Organized into 11 chapters, this book begins with an overview of the recognition of the various types of cardiomyopathy based on a detailed analysis of function and structure. This text then examines the structure of the amyloid fibril and the pattern of deposition of it in the body. Other chapters consider the possible link be.